Continuous reproduction under a bimodal precipitation regime in a high elevation anole (anolis mariarum) from antioquia, colombia (2011)
Reproductive activity was studied in two populations of Anolis mariarum duringrainy and dry season months in the Antioquia department of Colombia. Minimumsize at maturity was comparable at the two sites for both males (37-39 mm SVL) andfemales (44 mm SVL). At the population level, reproduction was continuous, with themajority of adult males and females reproductively active even during the dry seasonmonths. Juvenile size distributions also were uniform across seasons, consistent withthe conclusion that recruitment is not pulsed in these populations. However, therewas some evidence that certain females may lower their reproductive rates during thedry season, especially at the site receiving the least total annual precipitation (1700mm). These results further support accumulating evidence that populations of Anolisspecies inhabiting the climatic equator region, where the annual precipitation regimeis bimodal, are capable of maintaining continuous reproduction even when annualprecipitation amounts are relatively low. In contrast, Anolis populations in areasreceiving comparable amounts of annual precipitation during a single rainy seasontend to cease reproductive activity during the longer dry season each year.